2019
DOI: 10.2220/biomedres.40.107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor imagery combined with action observation training on the lateral specificity of muscle strength in healthy subjects

Abstract: Unilateral training of both lateral limbs increases unilateral muscle strength, whereas bilateral training increases bilateral muscle strength, a phenomenon known as lateral specificity in resistance training. Although motor imagery (MI) combined with action observation (AO) (i.e., MI + AO) training increases muscle strength, it is not completely understood whether such training increases the lateral specificity of muscle strength in a way resistance training does. To investigate whether MI + AO induces latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The first is the potential impact of the imagery effect from watching the videos in the SUKUBARA ® exercise protocol. In a previous study involving young participants, watching videos of high-intensity resistance exercises led to increased muscle strength in the specific muscle groups even without performing the actual exercises [28]. This phenomenon has been attributed to the effects of both motor imagery and action observation (observational learning).…”
Section: Discussionmentioning
confidence: 86%
“…The first is the potential impact of the imagery effect from watching the videos in the SUKUBARA ® exercise protocol. In a previous study involving young participants, watching videos of high-intensity resistance exercises led to increased muscle strength in the specific muscle groups even without performing the actual exercises [28]. This phenomenon has been attributed to the effects of both motor imagery and action observation (observational learning).…”
Section: Discussionmentioning
confidence: 86%
“…Studies have delivered AOMI interventions over short- (e.g., Bek et al, 2019) and longer-term (e.g., Shimada et al, 2019) periods when investigating their effects on movement outcomes. Meta regression analysis was used in the Movement meta-analysis to assess the relationship between intervention volume (total minutes) and the effects of AOMI on movement outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…This research has been conducted in sport (e.g., Romano-Smith et al, 2019) and rehabilitation (e.g., Scott et al, 2018) contexts, with neurotypical (e.g., Di Rienzo et al, 2019) and neurodivergent (e.g., Marshall et al, 2020) populations. The existing literature has almost exclusively demonstrated that movement outcomes are improved for different motor skills after AOMI interventions when compared to control conditions (e.g., Marshall et al, 2019; Romano-Smith et al, 2018; Shimada et al, 2019). However, comparisons with AO and MI interventions are equivocal, with some studies showing greater improvements in movement outcomes for AOMI compared to AO (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…AO + MI instructions have further been used to successfully counteract a pain-induced reduction in cortico-motor excitability (Larsen et al, 2019;see Suso-Martí et al, 2020), while AO + MI treatment has also been recommended for reducing adverse effects on the motor system following immobilisation-induced hypoactivity (Monany et al, 2022). Positive results of AO + MI treatment have additionally been obtained in muscular rehabilitation following hip replacement (Marusic et al, 2018; for related studies on strength training with healthy participants, see Shimada et al, 2019;di Rienzo et al, 2019). Finally, there is evidence of the potential benefits of using AO + MI instructions in brain-computer interface paradigms (e.g.…”
Section: Ao + MI Training In Motor Rehabilitationmentioning
confidence: 98%